A first-principles study of the structural and electronic properties of the epitaxial Ge(111)/La2O3(001) heterostructure - Liu, Kai; Ko, Eunjung; Hwang, Cheol Seong; Choi, Jung-Hae (IOP PUBLISHING LTD, 2019)
The effects of the atomic configuration of the epitaxial Ge(1 1 1)/La2O3(0 0 1)interface on the electrical properties of the structure were studied using first-principles calculations. The interface stability of this heterostructure is susceptible to the atomic configuration of the interface. The Ge-O-bonded interface without interfacial gap states is generally more stable than the Ge-La-bonded interface, which involves interfacial gap states. The band alignment is affected by the charge transfer depending on the interface atomic configuration, and the band bending across the La2O3 region was observed due to the electronic dipole inside the La2O3.
Keywords: PASSIVATION; DEFECTS